SI-BENING: SIMULATION-BASED FIRST AID TRAINING INNOVATION TO IMPROVE COMMUNITY KNOWLEDGE IN EARLY DETECTION AND FIRST AID FOR HYPOGLYCEMIA - Rahmalia Amni; Fikriyanti Fikriyanti; Abul A'la Tarigan (Universitas Kadiri, 2026)
Hypoglycemia is an emergency condition that requires fast and appropriate treatment. Currently, public knowledge in conducting early detection and first aid is very limited. Training with educational methods is less effective in increasing public knowledge, because it does not involve the community in real life. Therefore, simulation-based training is believed to be more effective in increasing public knowledge. The purpose of this study is to analyze the effectiveness of Si-Bening (Simulation-Based First Aid Training) on ​​public knowledge in conducting early detection and first aid for hypoglycemia emergency conditions. The research method is quasi-experimental with one group pre-post test without control and the research sample was 105 teachers in Banda Aceh City using convenience sampling technique. Data were analyzed using the Wilcoxon Signed-Rank test. Result showed that the majority of respondents had sufficient first aid knowledge (57.1%) and early detection was lacking (42.9%). After the intervention, the majority had high first aid knowledge (95.2%) and high early detection (94.3%). Significant improvements were seen in both early detection knowledge (Z = –8.710; p < 0.05) and first aid (Z = –8.556; p < 0.05). Training using the Si-Bening method effectively improved community skills related to early detection and first aid for hypoglycemia. It is recommended that further research utilize the Si-Bening method.